Haggai, Zechariah, Malachi - Coggins, Robert J. (Sheffield, UK Sheffield Academic, 1996)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. Haggai -- commentaries; Bible. O.T. Zechariah -- commentaries; Bible. O.T. Malachi -- commentaries